Safety and Sustainability Aspects of Food Packaging. - Jaiswal, Swarna (Elsevier Science & Technology, 2025)
Safety and Sustainability Aspects of Food Packaging is a volume in the Sustainable Food Packaging series and serves as a comprehensive guide to the multifaceted world of food packaging. Organized into three sections, this book explores critical aspects of packaging safety, sustainability, and regulatory compliance.
Keywords: elektronické knihy; electronic books